The person undergoing partial hip prosthesis: Case Report - Helena Teixeira; Magali Palma; João Vítor Vieira; Maria José Bule (Associação Portuguesa dos Enfermeiros de Reabilitação, 2021)
Introduction: Femoral fracture is a trauma that often occurs as a result of a fall, especially in the elderly. The specialist nurse in rehabilitation nursing is a professional with skills that aim at restoring functionality, minimizing disability and dependence and increasing autonomy and quality of life. Objective: To identify the gains from a rehabilitation program directed at the person who underwent partial hip replacement during admission to a Convalescence Unit. Method: Descriptive case study according to the guidelines of CAse REport (CARE). After identifying the musculoskeletal changes, functionality and definition of diagnoses, an individualized rehabilitation program was implemented and aimed at objectives and diagnoses, highlighting interventions for functional motor reeducation and the training of daily life activities. Results: An increase in the muscular strength of the lower and upper limbs, an increase in the joint amplitude of the joints of the lower limbs, an improvement in self-care walking with a walking aid and transfer, and a reduction in the risk of falling were proven. Conclusions: The results reveal the effectiveness of rehabilitation nursing interventions in the person submitted to partial hip replacement, in terms of strength and range of motion and in the execution and intensity of gait.